A virtual laboratory using high resolution crystal plasticity simulations to determine the initial yield surface for sheet metal forming operations. (May 2016) - Zhang, Haiming; Diehl, Martin; Roters, Franz; Raabe, Dierk
Abstract: We present a virtual laboratory to investigate the anisotropic yield behavior of polycrystalline materials by using high resolution crystal plasticity simulations. Employing a fast spectral method solver enables us to conduct a large number of full-field virtual experiments with different stress states to accurately identify the yield surface of the probed materials. Based on the simulated yield stress points, the parameters for many commonly used yield functions are acquired simultaneously with a nonlinear least square fitting procedure. Exemplarily, the parameters of four yield functions frequently used in sheet metal forming, namely Yld91, Yld2000-2D, Yld2004-18p, and Yld2004-27p are adjusted to accurately describe the yield behavior of an AA3014 aluminum alloy at two material states, namely with a recrystallization texture and a cold rolling texture. The comparison to experimental results proves that the methodology presented, combining accuracy with efficiency, is a promising micromechanics-based tool for probing the mechanical anisotropy of polycrystalline metals and for identifying the parameters of advanced yield functions. Highlights: High resolution crystal plasticity simulations are applied to study the yield behavior of polycrystalline materials. A spectral solver enables us to conduct a large number of virtual tests to identify the yield surface of the probed materials. The yield behavior of an AA3014 aluminum alloy at two material states is investigated in detail. The parameters of four frequently used yield functions are acquired.